Calidad Del Aire Y Emisiones De La Industria Ladrillera En Ciudad Bolívar: Hacia El Desarrollo De Herramientas De Apoyo Y Soluciones Integradas (2024)
In Colombia, industrial growth has contributed to the use of fossil fuels, which has generated both social and environmental repercussions, and air pollution has caused significant damage to ecosystems and public health. In Ciudad Bolívar, although brick kilns are a source of employment and economic development, they have released pollutants such as fine particles, sulfur dioxide, carbon monoxide, and volatile organic compounds, worsening air quality. The combination of this pollution with emissions from other industries has resulted in alarming levels of suspended particles, severely affecting Bogotá.